Катализ радиационно-стимулированных процессов в АТМ металлами и полупроводниками - Макеев М. А. Михаил Алексеевич; Адушев Г. П. Геннадий Павлович; Суровой Э. П. Эдуард Павлович; Супонина Н. В. Наталья Владимировна (1985, 1985)
Деп. в ОНИИТЭХим г. Черкассы 21.08.85, № 863-ХП-85.